2005
DOI: 10.1158/1078-0432.ccr-05-1068
|View full text |Cite
|
Sign up to set email alerts
|

Apurinic/Apyrimidinic Endonuclease Activity Is Associated with Response to Radiation and Chemotherapy in Medulloblastoma and Primitive Neuroectodermal Tumors

Abstract: Purpose: Apurinic/apyrimidinic endonuclease (Ap endo) is a key DNA repair activity that confers resistance to radiation-and alkylator-induced cytotoxic abasic sites in human cells. We assayed apurinic/apyrimidinic endonuclease activity in medulloblastomas and primitive neuroectodermal tumors (PNET) to establish correlates with tumor and patient characteristics and with response to adjuvant radiation plus multiagent chemotherapy. Experimental Design: Ap endo activity was assayed in 52 medulloblastomas and 10 PN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 41 publications
7
97
0
Order By: Relevance
“…Our results are supported by those of others in that the suppression of APE1 results in hypersensitivity to chemotherapeutic agents (10,26,27). Additionally, targeted reduction of Ape1/Ref-1 protein by specific anti-sense oligonucleotides renders mammalian cells hypersensitive to methylmethane sulfonate (MMS), H 2 O 2 , bleomycin, temozolomide (TMZ) and gemcitabine (22,28,29). Moreover, Robertson and colleagues found that elevated expression of APE1 in testicular cancer cell lines results in resistance to certain therapeutic agents, such as bleomycin and radiation (21).…”
Section: Cell Cycle Perturbations Aftersupporting
confidence: 88%
See 1 more Smart Citation
“…Our results are supported by those of others in that the suppression of APE1 results in hypersensitivity to chemotherapeutic agents (10,26,27). Additionally, targeted reduction of Ape1/Ref-1 protein by specific anti-sense oligonucleotides renders mammalian cells hypersensitive to methylmethane sulfonate (MMS), H 2 O 2 , bleomycin, temozolomide (TMZ) and gemcitabine (22,28,29). Moreover, Robertson and colleagues found that elevated expression of APE1 in testicular cancer cell lines results in resistance to certain therapeutic agents, such as bleomycin and radiation (21).…”
Section: Cell Cycle Perturbations Aftersupporting
confidence: 88%
“…Recent evidence indicated that APE1/Ref-1, the key enzyme in BER pathway, may be a crucial determinant of chemotherapy sensitivity (16)(17)(18)(19)(20)(21)(22). In several tumors, APE1/ Ref-1 subcelluar localization has been demonstrated to have a prognostic value or to correlate with aggressiveness (16,23,24).…”
Section: Cell Cycle Perturbations Aftermentioning
confidence: 99%
“…43), and a central BER component such as APE1, would elicit a more pronounced cytotoxic response to BCNU than single protein -targeted paradigms. Notably, the results of others support the notion that the APE1 repair nuclease capacity is a determinant in BCNU resistance, particularly in brain tumors (21,44).…”
Section: Discussionmentioning
confidence: 72%
“…[17][18][19][20][21][22][23][24]. These findings reveal a prominent role for APE1 in the repair of specific oxidative, alkylation, and enzymatic DNA intermediates, and identify this protein as a potential target for certain therapeutic paradigms.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the earliest work, published by Kelley and colleagues, revealed that APE1 provides resistance against not only MMS and hydrogen peroxide, but also the anti-cancer agents thiotepa, etoposide, and ionizing radiation (221). Through the efforts of many labs since, there is a general consensus emerging that indicates a role for APE1 in dictating cellular responsiveness to clinically relevant alkylators, most notably temozolomide (7,14,137,142,193), and a subset of chain-terminating nucleoside analogs, most prominently troxacitabine (114,137,180). Such a role is consistent with the biochemical activities of APE1, as alkylating agents, particularly mono-functional versions, induce a high number of abasic sites through both direct and indirect mechanisms, and certain anti-metabolites generate exonuclease 3¢-end substrates.…”
Section: Protein Depletionmentioning
confidence: 99%